2021
DOI: 10.3390/su132212578
|View full text |Cite
|
Sign up to set email alerts
|

Pressurized Liquid Extraction of Polyphenols and Anthocyanins from Saffron Processing Waste with Aqueous Organic Acid Solutions: Comparison with Stirred-Tank and Ultrasound-Assisted Techniques

Abstract: Fοllow up with our previous study on the extraction of saffron processing waste polyphenols using deep eutectic solvents, the objective of this examination was a comparative evaluation of pressurized liquid extraction (PLE), stirred-tank extraction (STE) and stirred-tank extraction with ultrasonication pretreatment (STE/UP) with respect to the recovery of pigments and antioxidant polyphenols from saffron processing waste. Aqueous solutions of citric and lactic acids at two different concentrations were used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…From our bibliographic survey, five studies exploited the PLE technique with green solvents to extract anthocyanins from different matrices, such as saffron [22], black bean [25], jabuticaba [27], and red grape [40,41,44]. All studies agreed that the pressure did not significantly affect the extraction yield, while the temperature was the most important variable since it influenced both the polarity and the solubility.…”
Section: Pressurized Liquid Extractionmentioning
confidence: 95%
See 2 more Smart Citations
“…From our bibliographic survey, five studies exploited the PLE technique with green solvents to extract anthocyanins from different matrices, such as saffron [22], black bean [25], jabuticaba [27], and red grape [40,41,44]. All studies agreed that the pressure did not significantly affect the extraction yield, while the temperature was the most important variable since it influenced both the polarity and the solubility.…”
Section: Pressurized Liquid Extractionmentioning
confidence: 95%
“…Water, either pure or mixed with other solvents, emerged as the solvent of choice for the green recovery of anthocyanins in several cases. For the valorization of saffron (Crocus sativus L.) by-products, four out of five studies used just water or acidified water [19,[21][22][23]. The only one that did not report the use of water applied cold pressing, which is actually a solvent-free technique [20].…”
Section: Watermentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration-dependent extraction (0.1, 0.2, and 0.3%) revealed that 0.3% concentrations of these acids resulted in a higher yield of anthocyanin; however, higher or lower concentrations than 0.3% resulted in lower yields [ 51 ]. Similarly, based on the current observations, Pappas, Athanasiadis, Palaiogiannis, Poulianiti, Bozinou, Lalas and Makris [ 34 ] conducted a proportional evaluation of diverse novel technologies for the extraction of total anthocyanins from freeze-dried saffron tepals using aqueous solutions of citric acid and the lactic acid at various concentrations. Contrastingly, these results showed that no specific configuration was observed for the type of acid or concentration.…”
Section: Resultsmentioning
confidence: 99%
“…The existing literature regarding the production, extraction and analytical aspects of natural pigments developed for PBM is very limited; however, some corresponding studies have been reported [ 13 , 22 , 29 , 32 , 33 , 34 ]. Therefore, researchers are taking a profound interest in utilizing natural pigments as replacements for their synthetic counterparts, particularly by developing sustainable extraction techniques for the efficient retrieval of bioactive compounds for use in PBM products and nutraceuticals.…”
Section: Introductionmentioning
confidence: 99%